2019
DOI: 10.1039/c8sc04389b
|View full text |Cite
|
Sign up to set email alerts
|

CO2 capture by Mn(i) and Re(i) complexes with a deprotonated triethanolamine ligand

Abstract: CO2 capture at low concentration by catalysts is potentially useful for developing photocatalytic and electrocatalytic CO2 reduction systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 58 publications
0
32
0
3
Order By: Relevance
“…Koizumi et al. used deprotonated triethanolamine as a monodentate ligand on their Mn–bpy complexes to capture carbon dioxide [95] . The reversible insertion of CO 2 into the Mn−O bond according to the proposed mechanism (Scheme 10) occurred with an equilibrium constant >1000 and was confirmed by NMR and IR spectroscopy as well as DFT calculations.…”
Section: Transition Metal Complexes As Catalysts In Electrochemical Co2 Reductionmentioning
confidence: 97%
“…Koizumi et al. used deprotonated triethanolamine as a monodentate ligand on their Mn–bpy complexes to capture carbon dioxide [95] . The reversible insertion of CO 2 into the Mn−O bond according to the proposed mechanism (Scheme 10) occurred with an equilibrium constant >1000 and was confirmed by NMR and IR spectroscopy as well as DFT calculations.…”
Section: Transition Metal Complexes As Catalysts In Electrochemical Co2 Reductionmentioning
confidence: 97%
“… Möglicher Mechanismus der CO 2 ‐Insertion in die Mn‐O‐Bindung (R=CH 2 CH 2 OH) [95] . Veröffentlicht von der Royal Society of Chemistry.…”
Section: üBergangsmetallkomplexe Als Katalysatoren In Der Elektrochemischen Co2‐reduktionunclassified
“…Koizumi et al verwendeten deprotoniertes Triethanolamin als einzähnigen Liganden an ihren Mn-bpy-Komplexen, um Kohlendioxid einzufangen. [95] Die reversible Insertion von CO 2 in die Mn-O-Bindung nach dem vorgeschlagenen Mechanismus (Schema 10) erfolgt mit einer Gleichgewichtskonstante > 1000 und wurde durch NMR-und IR-Spektroskopie sowie DFT-Rechnungen bestätigt. Die Umwandlung des koordinierten Substrats wurde in diesem Bericht jedoch nicht behandelt.…”
Section: Gruppe 7-m N Reunclassified
See 1 more Smart Citation
“…have been studied extensively for the homogeneous electrocatalytic and photocatalytic reduction of carbon dioxide. [4][5][6][7][8][9][10][11][12][13][14][15] Apaydinet al 7 reported a excellent comprehensive overview on homogeneous and heterogeneous CO 2 reduction catalyzed by organic, organometallic and bioorganic systems. Mechanistic details for the CO 2 reduction processes undertaken by electrochemical, bioelectrochemical and photoelectrochemical approaches are thoroughly analyzed.…”
Section: Introductionmentioning
confidence: 99%